Legal Protection of Copyright in social media: Instagram Case Study - Soliha, Jamaliyatus; Widya Pratikno, Ardhita; Nur Ichwan Hidayat, Achmad; Reza Adiyanto, Mochamad (Lafadz Jaya Publisher, 2023)
This research illustrates that the use of technology, especially the internet, is currently experiencing extraordinary development which includes the use of social media as a means of communication and self-expression. One of them is Instagram social media, a platform that is currently experiencing significant growth and trends in Indonesia. The focus of this research is on legal protection for Instagram users regarding copyrights owned by rights holders for images uploaded on the platform. The research uses normative juridical methods by relying on secondary data. The research results show that there is a form of legal protection for Instagram users regarding the copyright of uploaded images. This protection is regulated based on the provisions of applicable laws and regulations. In conclusion, the legal basis contained in the Law provides a clear framework for protecting the rights of creators regarding images or visual works uploaded on platforms such as Instagram.